Effect of ceftriaxone on blood pressure, respiration and its analgesic and antipyretic activities - Mohamed Aboubakr; Mossad Elsayed; Ashraf Elkomy (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine the effect of ceftriaxone on blood pressure and respiration in dog. In addition, analgesic and antipyretic activities of ceftriaxone were investigated in mice and rats. Materials and Methods: Effect of different doses of ceftriaxone (26.66, 53.33, 106.66 mg/kg, IV) on blood pressure and respiration rate were determined in anesthetized dogs. Analgesic and antipyretic activities of two different doses of ceftriaxone were investigated in mice and rats, respectively. Results: Ceftriaxone had no effect on blood pressure and rate of respiration in anesthetized dogs. However, ceftriaxone (260 and 520 mg/kg) had a significant analgesic effect for four hours and had a significant antipyretic effect at 2.5 and 1.5 hours at doses of 180 and 360 mg/kg, respectively. Conclusion: Ceftriaxone is preferable in bacterial infections or feverish conditions owing to its antibacterial, antipyretic and analgesic activities.